Harnessing Economic Opportunities: Business and Blockchain Technology Introduction for Communities - Kora Fitra Putri Oganda; Naomi Lyraa; Greisy Jacqueline (Blockchain Frontier Technology, 2024)
This research aims to investigate the potential utilization of economic opportunities through the introduction of business and blockchain technology within the community. The research methodology involves literature analysis, interviews with relevant stakeholders, and the implementation of business and blockchain technology concepts on a small scale as a case study. The literature analysis provides in-depth insights into how the implementation of blockchain technology can broaden economic opportunities across various sectors. Stakeholder interviews engage local business players, technology experts, and community representatives to obtain a comprehensive perspective. The practical implementation of business and blockchain technology concepts on a small scale offers a hands-on understanding of the potential benefits and challenges that the community may encounter in leveraging these economic opportunities. Discussions involve the evaluation of implementation, identification of barriers, and recommendations for further development. The research findings underscore that the introduction of business and blockchain technology can serve as a vital catalyst for stimulating community economic growth. The conclusion of this study encourages a deeper understanding of the potential and challenges of implementing this technology and formulating strategies that support community economic development through the utilization of available opportunities.